(untitled) (Scientific journal of the Fergana State University, 2026)
The article examines the essence and social significance of such concepts as "position", "vital position", "social position", "active position". The role of active social position of young people in the process of building a civil society, building a legal democratic state and modernization in the conditions of the new Uzbekistan is revealed. The active social position is analyzed as an important factor in the formation of the consciousness of modern youth, and the importance of the young people’s desire for innovation and the rise of their intellectual potential is considered.